Cover Image, Volume 234, Number 6, june 2019. Issue 6 (21st February 2019) - Shang, Jin; He, Qianxin; Chen, Ying; Yu, Dahai; Sun, Lulu; Cheng, Genyang; Liu, Dong; Xiao, Jing; Zhao, Zhanzheng
Abstract : Cover : The cover image is based on the Original Research Article miR‐15a‐5p suppresses inflammation and fibrosis of peritoneal mesothelial cells induced by peritoneal dialysis via targeting VEGFA by Jin Shang et al., DOI: 10.1002/jcp.27660 .